Achievement and Goals in Private Music Learning: Pathways to Motivation and Musical Growth - Piter Sembiring; Tia Destiana Puri (Jurnal Pendidikan Non formal, 2025)
This study examines how achievement orientations, goal setting practices, and motivational factors shape students’ engagement and musical development in private music learning. Using a qualitative design, data were collected through observations and semi structured interviews with twelve students aged eight to seventeen studying various instruments in one-to-one lessons. The findings show that mastery and performance orientations emerge through structured tasks, diagnostic-based sequencing, and individualized guidance. Clear short term and long term goals enhanced students’ focus and supported consistent practice routines, while teacher support and joyful learning principles helped sustain motivation when students faced technical challenges. Motivational barriers generally stemmed from task difficulty, unmet expectations, or irregular home practice but were mitigated through gradual task breakdown and targeted instruction. The study concludes that aligning achievement orientations, structured goal setting, and motivational supports is essential for maintaining engagement and promoting continuous musical growth in private music education.